2014
DOI: 10.1093/brain/awt355
|View full text |Cite
|
Sign up to set email alerts
|

HTT-lowering reverses Huntington’s disease immune dysfunction caused by NFκB pathway dysregulation

Abstract: Huntington's disease is an inherited neurodegenerative disorder caused by a CAG repeat expansion in the huntingtin gene. The peripheral innate immune system contributes to Huntington's disease pathogenesis and has been targeted successfully to modulate disease progression, but mechanistic understanding relating this to mutant huntingtin expression in immune cells has been lacking. Here we demonstrate that human Huntington's disease myeloid cells produce excessive inflammatory cytokines as a result of the cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
172
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(185 citation statements)
references
References 62 publications
(81 reference statements)
11
172
2
Order By: Relevance
“…Monocytes and monocyte-derived macrophages obtained from blood collected from HD patients express mutant HTT but do not show increased pro-inflammatory cytokines expression and/or production compared with monocytes obtained from healthy donors [12,34,85]. However, these cells are hyperactive in response to an external pro-inflammatory stimulation [12,85].…”
Section: Monocytes and Macrophages In Hd Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes and monocyte-derived macrophages obtained from blood collected from HD patients express mutant HTT but do not show increased pro-inflammatory cytokines expression and/or production compared with monocytes obtained from healthy donors [12,34,85]. However, these cells are hyperactive in response to an external pro-inflammatory stimulation [12,85].…”
Section: Monocytes and Macrophages In Hd Neuroinflammationmentioning
confidence: 99%
“…However, these cells are hyperactive in response to an external pro-inflammatory stimulation [12,85]. Upon LPS stimulation in vitro , mutant HTT in myeloid cells binds IKKγ and results in increased NF-κB activity, likely explaining the altered transcription of NF-κB target genes, and RNAi of HTT reverses the effects associated with NF-κB dysregulation [85]. Monocytes from HD individuals display phenotypic heterogeneity in terms of M1–M2 polarization throughout the clinical course of the disease [86].…”
Section: Monocytes and Macrophages In Hd Neuroinflammationmentioning
confidence: 99%
“…In the peripheral immune system, mutant huntingtin also impacts inflammatory responses through inhibition of NF-kB signaling (Träger et al 2014). Signaling through CB2 cannabinoid receptors might also explain inflammation in HD (Palazuelos et al 2009;Bouchard et al 2012).…”
Section: Astrocyte and Microglial Dysfunction In Hdmentioning
confidence: 99%
“…Most of this work has been carried out in peripheral blood or ex vivo cells [58] but in 2007 Dalrymple and colleagues found that plasma elevations of clusterin were mirrored in CSF from 20 patients and 10 controls in the first report from a CSF collection with dedicated matched contemporaneous healthy controls from the general population, rather than from patients under investigation for other conditions [12]. Their finding of elevated IL-6 and IL-8 in blood plasma was reproduced in patient CSF in 2008 by Björkqvist, et al [15].…”
Section: Inflammatory Markersmentioning
confidence: 99%